UJI COBA PENANAMAN MANGROVE DI BEKAS TAMBAK BUDIDAYA UDANG DI KABUPATEN PEMALANG - Sri Puryono KS. (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
The acceleration of mangrove deforestationhas become an issue ofgreat concernfor several yecirs in the world. Factors responsible for the depletion of the mangroveforest included mangrove clearing for human settlement, commercial shrimp and prawn hatcheries, salt production. industry,recreationarea, and an harbor arefor mangrove environ/menbetterment. Theplantation trial for reboisation was started at Pemalang District. Therewere technical problems in this activity such as: low level and, high salinity, unsmokly streamflow eel. Based on the view of "Good Tree Grows in The Right Land ", the research was aimed tofind the right species to be planted in ex-shrimp/arm area. The research was done at apremilinarystage, wherefour species wereplanted in the land a different altitude of 10 cm in 16 terraces.